THE EFFECTIVENESS OF POJK 23/2022 AND IMPLICATIONS FOR MSME FINANCING INCLUSION (EVIDENCE FROM BPRS BTB BOGOR, WEST JAVA) - Saputra, Yusup; Isman, Isman; Salsabila, Azka (istinbath, 2025)
This study examines the impact of implementing POJK No. 23 of 2022 on MSME lending at BPRS Tegar Beriman Bank in Bogor Regency, with a particular focus on the effectiveness of the minimum financing limit policy in promoting the financial inclusion of non-bank MSMEs (the unbankable community). BPRS Tegar Beriman was selected as a representative of rural banks based on APBD. The methodology employed is a mixed-methods approach, incorporating an ex post quantitative analysis through linear regression of data collected from January 2023 to March 2024. The dependent variable in this study is total financing to non-bank third parties, while the independent variables include murabaha, istishna, and multijasa receivables. The regression results indicate an R-square of 0.82359, suggesting that the model accounts for 82.36% of the observed variation in financing. Of the three variables, only istishna financing is statistically significant, with a negative coefficient. It suggests that banks are exercising caution when facilitating complex project financing. Theoretically, this finding is indicative of the preeminence of prudential logic in legal substance, the accommodation of community needs within legal culture, and structural efficiency resulting from regulatory pressure in the legal structure, as posited by Lawrence Friedman's theory. Bank adjustments to regulations are regarded not only as a form of normative compliance but also as a strategic effort to enhance risk management efficiency and achieve financing targets. The minimum lending regulation has been shown to affect bank compliance with it positively.